Analisis Yuridis Terhadap Eksekusi Putusan Kewajiban Pemberian Nafkah Anak di Bawah Umur Akibat Perceraian Orang Tua (Studi Pengadilan Agama Medan) - Marilin, Eka Irwan; Ahmad, Akiruddin; Sahbudi, Sahbudi (Jurnal Ilmiah Penegakan Hukum, 2025)
Living together is an essential characteristic of human existence, including within the family context. However, divorce often raises issues related to the fulfillment of children's rights, particularly child support. This study aims to: 1) analyze the legal provisions regarding the execution of child support decisions for minors as a consequence of divorce; 2) examine the mechanism for implementing child support decisions in religious court practice; and 3) identify the obstacles faced by Religious Courts and their implications for the protection of children's rights. The study used a case study approach with qualitative descriptive methods. Data were obtained through interviews and observations with authorities at the Medan Religious Court, including judges, court clerks, junior law clerks, and bailiffs. The results indicate that obstacles to the execution of child support decisions are influenced by internal and external factors. Internal factors include the judge's limited authority to compel the losing party and the formalistic and time-consuming execution procedures. External factors include low legal awareness, weak economic conditions, bad faith on the part of the party owing child support, and limited supervisory facilities. These obstacles impact the effectiveness of post-divorce child rights protection.